Bacteriocuprein superoxide dismutases in pseudomonads. - Steinman, H M (1985)
Two new instances of the rare bacteriocuprein form of superoxide dismutase have been discovered in Pseudomonas diminuta and P. maltophilia. Each species contains a manganese superoxide dismutase as well. Eight other strains of Pseudomonas and Xanthomonas spp. lacked bacteriocupreins and contained either a manganese or an iron superoxide dismutase. Native molecular weights and isoelectric points were determined for all these bacterial dismutases. A monospecific polyclonal antibody was prepared against the bacteriocuprein from Photobacterium leiognathi; it was not cross-reactive with the bacteriocuprein from either Pseudomonas strain. Bacteriocupreins have previously been identified in only two procaryotes, P. leiognathi and Caulobacter crescentus. The discovery of the Pseudomonas bacteriocupreins reveals a broader distribution, raising the possibility that bacteriocupreins are a continuous line of descent among procaryotes and not isolated evolutionary occurrences, as previous data suggested.